In vivo Whole-Cell Recordings Combined with Electron Microscopy Reveal Unexpected Morphological and Physiological Properties in the Lateral Nucleus of the Trapezoid Body in the Auditory Brainstem - Franken, Tom P.; Smith, Philip H.; Joris, Philip X. (Frontiers in Neural Circuits, 2016)
The lateral nucleus of the trapezoid body (LNTB) is a prominent nucleus in the superior olivary complex in mammals including humans. Its physiology in vivo is poorly understood due to a paucity of recordings. It is thought to provide a glycinergic projection to the medial superior olive (MSO) with an important role in binaural processing and sound localization. We combined in vivo patch clamp recordings with labeling of individual neurons in the Mongolian gerbil. Labeling of the recorded neurons allowed us to relate physiological properties to anatomy at the light and electron microscopic level. We identified a population of quite dorsally located neurons with surprisingly large dendritic trees on which most of the synaptic input impinges. In most neurons, one or more of these dendrites run through and are then medial to the MSO. These neurons were often binaural and could even show sensitivity to interaural time differences (ITDs) of stimulus fine structure or envelope. Moreover, a subpopulation showed enhanced phase-locking to tones delivered in the tuning curve tail. We propose that these neurons constitute the gerbil main LNTB (mLNTB), In contrast, a smaller sample of neurons was identified that was located more ventrally and that we designate to be in posteroventral LNTB (pvLNTB). These cells receive large somatic excitatory terminals from globular bushy cells. We also identified previously undescribed synaptic inputs from the lateral superior olive. pvLNTB neurons are usually monaural, display a primary-like-with-notch response to ipsilateral short tones at CF and can phase-lock to low frequency tones. We conclude that mLNTB contains a population of neurons with extended dendritic trees where most of the synaptic input is found, that can show enhanced phase-locking and sensitivity to ITD. pvLNTB cells, presumed to provide glycinergic input to the MSO, get large somatic globular bushy synaptic inputs and are typically monaural with short tone responses similar to their primary input from the cochlear nucleus.